FACTORS CAUSE LEARNING DIFFICULTIES AUTOMOTIVE MECHANICS PROGRAM - Darul Prayogo; Bharto Ari Raharjo; Moh. Zaenal Arifin; Tony Santiko; Purwanti Purwanti; Ahmad Mauludin (Universitas Muhammadiyah Semarang, 2018)
The background of the problem in this research is the learning difficulties experienced by thestudents of class I Proggram of Mechanical Expert Automotive SMK N 5 Semarang academic year2016/2017 which indicated less than optimal learning achievement. This background becomes thebasis of research. The purpose of this study is to mengetehui level of difficulty belaajr students SMKN 5 Semarang, especially class I Automotive Mechanics Expertise Program. In addition, the mainobjective to be achieved is to determine the dominant factors that cause the difficulty of learninggrade 2 students of Automotive Mechanical Skill Program of SMK Negeri 5. In accordance with thepurpose of research into the study population is a class I in the academic year 2016/2017. Themethod of collecting dta used there is 2, that is documentation method to determine population. Inthis case the documentation is in the form of a list of student names. The second method is thequestionnaire method. Questionnaire was prepared using a lattice consisting of 33 sub factors and 66items. Based on the results of the test instrument performed by students of grade 3 MO 1 academicyear 2016/2017, the analysis results obtained 52 valid questions and 14 invalid questions. Ininstrument testing, the price of r11 is greater than the reference price of 0.30 so that the instrument isreliable and can be used as a test instrument. Then taken 33 questions sesui with sub factorrespectively. Data analysis technique used is descriptive analysis technique percentage. Thistechnique uses a comparison of the student scores with an ideal score. Overall the total score ofstudents studied is 2470 of the entire ideal score of 5280 or 46.78%. Based on predeterminedcriteria, this percentage belongs to less problematic category. Of the 32 respondents studied, all hadproblems learning in the less problematic category. The number of scores per sub-factor showsdifferent categories. Sub factor of family environment, society environment included in less problemcategory. While the sub-factor of the school environment into the category is quite problematic.Based on the results of the above research can be concluded that the level of difficulty learning siswamasuk dalm less problematic category. The cause of students' learning difficulties fromextracurricular factors is very dominant as a learning difficulty factor.For teachers should be as early as possible to identify the learning difficulties experienced bystudents so that it can help solve it. For SMK N 5 Semarang should always fix the condition of theschool so that the teaching and learning process can take place properly.Keywords: Learning Difficulties, Automotive Mechanics